Investigation of the presence of an aliphatic biopolymer in cyanobacteria: Implications for kerogen formation. (April 2015) - Biller, Patrick; Ross, Andrew B.; Skill, Stephen C.
Highlights: Two algae and a cyanobacterium investigated for algaenan presence. Chlorogloeopsis contains an aliphatic biopolymer similar to algaenan. Algaenan samples were analysed using Py–GC–MS and 13 C solid state NMR. Resistant biopolymer in Chlorogloeopsis discussed in context of kerogen formation. Abstract: Algaenan has been suggested to be one of the main precursors of certain kerogens. It is a non-hydrolysable and insoluble biomolecule of high molecular weight. It has been found in a limited number of microalgae species. There is considerable uncertainty about its formation and preservation, as well as its role in kerogen formation and the implications for the global C cycle. We tested whether the cyanobacterium Chlorogloeopsis fritschii can synthesise a biomacromolecule similar to algaenan with potential to contribute to kerogen via selective preservation. Two freshwater green microalgae, Pseudochoricystis ellipsoidea and Scenedesmus obliquus, as well as C. fritschii, were subjected to harsh solvent extraction and hydrolysis steps to obtain an insoluble and non-hydrolysable macromolecule. The residues from all three species were analysed using pyrolysis–gas chromatography–mass spectrometry and solid-state nuclear magnetic resonance spectroscopy. The analysis revealed that C. fritschii indeed contains a resistant biomacromolecule exhibiting the characteristic aliphatic structure of algaenan, similar to the algaenan residues from the two microalgae. Due to the robust nature of Chlorogloeopsis compared with eukaryotes, it can prevail in extreme environmental conditions such as freezing, thawing, desiccation and overheating – conditions prevalent on the primeval earth. The presence of a resistant aliphatic biopolymer in Chlorogloeopsis suggests that cyanobacteria could have contributed to kerogen via selective preservation.